Basic questions. (4th January 2018) - Carruthers, Peter
Abstract : This paper argues that a set of questioning attitudes are among the foundations of human and animal minds. While both verbal questioning and states of curiosity are generally explained in terms of metacognitive desires for knowledge or true belief, I argue (following Whitcomb and Friedman) that each is better explained by a prelinguistic sui generis type of mental attitude of questioning . I review a range of considerations in support of such a proposal and improve on previous characterizations of the nature of these attitudes. I then broaden their explanatory scope to include a number of forms of exploratory search. The paper has three main goals: (a) to characterize the nature of the questioning attitudes, outlining their causal role and type of content; (b) to argue that they are fundamental components of the mind, being widespread among animals and not constructed during ontogeny out of other attitudes; and (c) to suggest that they explain a great deal more behavior (among both humans and animals) than one might think.